Nestin as a marker beyond angiogenesis$nexpression pattern in haemangiomas and lymphangiomas - Mamilos, Andreas; Winter, Lina; Wiedenroth, Christoph B.; Niedermair, Tanja; Zimmer, Stefanie; Schmitt, Volker H.; Keller, Karsten; Topolčan, Ondrej; Karlíková, Marie; Rupp, Markus; Brochhausen, Christoph; López-Cotarelo Rodríguez-Noriega, Cristina (Biomedicines, 2025)
Background: The intermediate filament nestin was first described in stem and progenitor cells of neural and mesenchymal origin. Additionally, it is expressed in endothelial cells during wound healing and tumorigenesis. Thus, nestin is widely regarded as a marker for proliferative endothelium. However, little is known about its role in lymphatic endothelium. Methods: Here, we analyzed the expression of nestin in the endothelium of ten human haemangiomas and ten lymphangiomas in situ by immunohistochemistry. This study aimed to investigate the expression of nestin in haemangiomas and lymphangiomas to determine its potential role as a vascular marker. Specifically, we aimed to assess whether nestin expression is restricted to proliferating endothelial cells or also present in non-proliferative blood vessels. Results: Immunohistochemically, haemangiomas were positive for CD31 but negative for D2-40. The endothelial cells within these lesions showed a homogeneous expression of nestin. In contrast, the endothelium of lymphangiomas reacted positively for D2-40 and CD31 but did not show any nestin expression. Additionally, only a few endothelial cells of capillary haemangiomas showed a Ki-67 positivity. Conclusions: The differential expression of nestin in haemangiomas and lymphangiomas indicates a specificity of nestin for the endothelium of blood vessels. The Ki-67 negativity in the majority of the endothelial cells reveals the proliferative quiescence of these cells. These findings indicate that nestin could be used as a marker to differentiate between blood and lymphatic vessels.
Gesehen am 15.07.2025